Film Phenomenology and Adaptation: The "Fleshly Dialogue" of Jane Campion's In the Cut. (27th January 2018) - Richard, David Evan
Abstract: This article proposes that the philosophy and methodology of film-phenomenology offers a fresh perspective for the analysis of screen adaptation. In the article's first section, I explore why adaptation studies as a discipline has turned a blind eye to the subjective experience of screen adaptation, preferring modes of analysis that foreground adaptation as an objective intersection or layering of texts. But, as I suggest, any analysis of an adaptation is impoverished without also attending to their material texture. Using the theoretical insights of phenomenology—and how they have been taken up in film studies, particularly by scholar Vivian Sobchack—I probe the sensual contours of Jane Campion's 2003 film In the Cut, her adaptation of Susanna Moore's erotic-thriller novel. In doing so, the phenomenological method reveals how Campion makes palpable the experience of the novel's first-person narrator for the spectator in what I term 'tactile orientation.' The analysis of this case study reveals the broader value of the phenomenological method for screen adaptation and renews an appreciation of adaptations as works of art.